Measuring the Essence of Local Wisdom's value in the Behavior of Government Apparatuses in State Administration Institutions - Mohamad Ichsana Nur; Reni Qurroti Aeni; Tedi Juana (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This research aimed to examine how local wisdom's value was applied to government reform at the State Administration Institute (LAN) in Jatinangor, West Java. This study focuses on restructuring the government apparatus so that it can apply national ideals derived from the community in which it lives. This study uses a qualitative approach with a descriptive type of research. The data was obtained using the purposive sampling technique. This research shows that the State Administration Institution as an institution requires the right values. Must adopt these values to the area's cultural values and character, where the Jatinangor State Administration Institute (Puslatbang PKASN) has the value of local wisdom called SAHATE. The application of SAHATE as the value of local wisdom positively impacts the organizational climate of LAN Jatinangor. The application of these local values has a positive influence on the work environment. Namely, each employee is very concerned about the relationship between individuals. It can suppress individual and sectoral egos so that all employees can focus on organizational goals and not focus on individual or group interests.